2019
DOI: 10.1155/2019/6217548
|View full text |Cite
|
Sign up to set email alerts
|

The Liver X Receptor Is Upregulated in Monocyte-Derived Macrophages and Modulates Inflammatory Cytokines Based on LXRα Polymorphism

Abstract: Liver X receptors (LXRs) have emerged as important regulators of inflammatory gene expression. Previously, we had reported that an LXRα gene promoter polymorphism (-1830 T > C) is associated with systemic lupus erythematosus (SLE). Therefore, we assessed cytokine expression in relation to LXRα polymorphism in monocyte-derived macrophages from patients with SLE. Macrophages were obtained after 72 hours of culture of human monocytes supplemented with phorbol 12-myristate 13-acetate. Cells were transfected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…It has also been reported that long‐term LXR activation potentiates pro‐inflammatory cytokine secretion in LPS‐stimulated human macrophages (Fontaine et al., 2007). Others have reported that LXR activation does not alter the secretion of pro‐inflammatory cytokines in macrophages following inflammatory stimulation (Kim et al., 2019). In the context of bone remodeling, LXRs have been found to play a dual role on osteoblasts and osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that long‐term LXR activation potentiates pro‐inflammatory cytokine secretion in LPS‐stimulated human macrophages (Fontaine et al., 2007). Others have reported that LXR activation does not alter the secretion of pro‐inflammatory cytokines in macrophages following inflammatory stimulation (Kim et al., 2019). In the context of bone remodeling, LXRs have been found to play a dual role on osteoblasts and osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids could modulate the process of macrophage differentiation 28 . Targeting receptors associated lipid metabolism, such as peroxisome proliferator-activated receptor γ (PPARγ), 12/15-Lipoxygenase (12/15-LO), sphingosine-1phosphate (S1P) and liver X receptors (LXRs), was able to affect differentiation of monocytes and production of proin ammatory cytokines, which were related to TLR7 and TLR9 expression [29][30][31][32] . Furthermore, we observed strong associations between the differential metabolites, particularly the lipids, suggesting that these metabolites may participate in the same metabolic pathway, or biological process.…”
Section: Discussionmentioning
confidence: 99%
“…Through these effects, it mediates the decomposition transport and effluence of cholesterol, and plays a key role in regulating the occurrence and progression of foam cell formation [31][32][33][34][35][36][37]. In addition, PPAR-γ inhibits monocyte/macrophage activation, reduces inflammatory cell infiltration, and decreases the release of inflammatory factors [38][39][40]. Thus, it is closely related to the regulation of macrophage inflammation.…”
Section: Discussionmentioning
confidence: 99%